Elements of gamification in virtual learning environments: a systematic review - Tenório, Marcos Mincov (2018)
Information technologies have introduced several changes in teaching and learning environments. In this scenario, the gamification technique emerges as a promissing approach, considering the impact on the students’ motivation and appealing to their participation. This paper describes a systematic review addressing gamification in virtual learning environments (VLE), presenting an overview on how gamification has been applied in these scenarios. This review was based on papers published in highly scored journals in the field of computers in education. The papers were selected according to the gamification theme, and the content was analyzed and a state of the art built, according to the retrieved qualitative data. The results seem to reveal that there are significant gains derived from the adoption of gamification in VLE. However, some gains are not unanimous and it depends on how the elements are applied. This paper also suggests a basis for future work aiming at applying gamification in a VLE.